Crime Prevention Program in Resident of Brgy. 164 Talipapa in Caloocan City Amid COVID-19 Pandemic: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researchers conducted this study to determine if the crime prevention program implemented by Barangay 164 – Talipapa, Caloocan City, can be used to face the problem of crime during the pandemic. As Michael Tonry and David Farrington (1995) described, crime prevention programs refer to traditional deterrent, incapacitative, and rehabilitative strategies operated by law enforcement and criminal justice system agencies. Crime will not be eradicated in society, but it will be reduced through implementing a crime prevention program employing law enforcement and local government in the community. The researchers used the descriptive method with the aid of statistical methods. The researchers use this method to get information by interviewing and conducting survey questionnaires. The researchers conducted a survey questionnaire and interviewed 20 respondents, ten barangay officials and ten police officers employed in the said barangay. Most respondents were 26-50 years old and male, which shows that the police force is male-dominated. The implementation, LGU, and community support were regarded as “very effective.” Results show that the crime rate during the pandemic decreased, while the problems that affected the crime prevention program were regarded as “serious.” Lastly, the measures proposed to address the problems encountered were “highly recommended.”  The researchers recommend the strict implementation of a curfew and requesting the city government for frequent checks by the police and barangay personnel, increase police or barangay visibility in crime-prone areas, and invite police community affairs and development groups to collaborate with the barangay unit for crime prevention.